Micromonospora humi sp. nov., isolated from peat swamp forest soil - Apakorn Songsumanus; Somboon Tanasupawat; Chitti Thawai; Khanit Suwanborirux; Takuji Kudo (My University, 2010)
A novel actinomycete, strain P0402(T), was isolated from peat swamp forest soil collected in Thailand. Its taxonomic position was determined by using a polyphasic taxonomic approach. The chemotaxonomic characteristics of this strain matched those of the genus Micromonospora, i.e. the presence of meso-diaminopimelic acid and N-glycolyl muramic acid in the peptidoglycan, whole-cell sugar pattern D, phospholipid type II, and cellular fatty acid type 3b. Phylogenetic analysis based on 16S rRNA gene sequences revealed a close relationship between strain P0402(T) and Micromonospora coxensis JCM 13248(T) (99.0 % similarity), Micromonospora eburnea JCM 12345(T) (99.0 %), Micromonospora marina JCM 12870(T) (98.9 %), Micromonospora halophytica JCM 3125(T) (98.7 %), Micromonospora chalcea JCM 3031(T) (98.7 %), Micromonospora purpureochromogenes JCM 3156(T) (98.6 %) and Micromonospora aurantiaca JCM 10878(T) (98.5 %). It could be clearly distinguished from these type strains based on low levels of DNA-DNA relatedness and phenotypic differences. On the basis of the data presented, strain P0402(T) is suggested to represent a novel species of the genus Micromonospora, for which the name Micromonospora humi sp. nov. is proposed. The type strain is P0402(T) ( = JCM 15292(T) = PCU 315(T) = TISTR 1883(T)).
Keywords: Micromonospora; Muramic acid; Diaminopimelic acid; Genomics and Phylogenetic Studies